Sustainable agricultural intensification: a handbook for practitioners in east and southern Africa - Bekunda, Mateete A.; Hoeschle-Zeledon, Irmgard; Odhong, Jonathan (CAB International, 2022)
This book provides an insight into the background, lessons learned, and the methodology of facilitating the application of best-bet/best-fit agricultural technologies to smallholder farms in East and Southern Africa (ESA). All technologies highlighted within this book, except those on livestock feeding, were trialed and demonstrated in farmers' fields over an eight-year period [2012-2020] as part of the Feed the Future/USAID funded research-for-development Africa RISING ESA Project and supported by the CGIAR. The livestock feed technologies …